Enactive Management: Application of Clehes and Viplan - Garcia-De la Cerda, O; Garcia-Herrera, C (Emerald Group Publishing Ltd., 2011)
Purpose: The purpose of this paper is to deal with the learning and adaptation of those particular human beings that manage modern companies. They are challenged not only by a very high rate of change, which is common to all of us, but by the fact that they are responsible for the viability of organizations that deal with a far larger complexity. Design/methodology/approach: The methodologies used were self-observation and observation of the actors that constitute a company by means of CLEHES, an ontological tool, and VIPLAN, an epistemic reference. Both together help enabling communications and conversations in different contexts and domains that otherwise would have been cognitively inhibited. Findings: These tools have been used as an enactive management approach that has allowed the effective growth of a small organization, which is the focus of this paper. Practical implications: The paper contains useful thinking, enaction and reflecting on the awareness to conserve and change structural adjustments. Originality/value: The paper shows how crisscrossing between an ontological tool - CLEHES and an epistemic tool-VIPLAN permits enacting organizational communications and conversations between human beings as managers to take care of their organizations. © Emerald Group Publishing Limited.